Remodeling Intestinal Flora with Sleeve Gastrectomy in Diabetic Rats - Xiaofei Huang; Pan Weng; Huixin Zhang; Yingli Lu (Journal of Diabetes Research, 2014)
Objective. As a complicated symbiotic system, intestinal flora is reported closely related to the development of type 2 diabetes recently. Sleeve gastrectomy is one of the approaches of bariatric surgery and could improve blood glucose control in type 2 diabetes patients. This study was to explore the relationship between remodeled intestinal flora and glucose metabolism in diabetic rats. Methods. 20 male diabetic rats were operated; 10 of them underwent sleeve gastrectomy, and 10 of them underwent sham operation. Meanwhile 10 male normal rats underwent sleeve gastrectomy as control. The animals’ weight and FBG had been measured. The composition changes of intestinal flora were detected by 16S rDNA sequence analysis. Results. In diabetic rats, weight and fasting blood glucose decreased significantly after sleeve gastrectomy. However, there was no significant change for weight and blood glucose in normal rats after operation. The intestinal flora of diabetic rats reduced in the proportion of Firmicutes and increased in the proportion of Bacteroidetes after sleeve gastrectomy. Conclusion. The change of dominant microorganisms in intestinal flora might play an important role in the glucose metabolism.